The impact of habitat conditions on blooming of Helichrysum arenarium (L.) Moench - Anna K. Sawilska (Acta Agrobotanica, 2012)
Helichrysum arenarium (L.) Moench is a perennial belonging to the Asteraceae family. It is used as a herb material. The species is under partial protection. The aim of the study was to determine the influence of the community type and weather conditions on blooming of everlasting. Growth and development dynamics vs. habitat factors were analyzed in detail. The results of this study indicate that blooming process of everlasting populations remains under influence of habitat factors, which is evidenced by a decrease of potential fertility paralleled by an increase of number of taxa found in phytocoenosis. Blooming process is also modified by weather conditions: the potential fertility index is significantly correlated with precipitation.